Nicknamen International: on the Way to Internet Anthroponymy - V. V. Kaziaba (Научный диалог, 2019)
The article introduces readers to the international collective monograph “Nicknamen international. Zur Namenwahl in sozialen Medien in 14 Sprachen” devoted to the description of nickname corpora from social media in 14 different countries, followed by a contrastive analysis. The article covers the idea and history of the work, its structure, methodology, style, language and features of the presentation, members of team of the authors. The main results, advantages and disadvantages of the study are briefly summarized.